Positioning of pneumatic artificial muscle under different temperatures - Sárosi József (Review of faculty of engineering : analecta technica Szegedinensia, 2010)
Some researchers have mentioned that temperature creates an important part in the accuracy of positioning of pneumatic artificial muscles (PAMs). However, in literature investigations for measuring temperature inside and outside the PAMs have not been found. This paper presents our robust motion control of these muscle actuators under different temperatures using slidingmode control.